2018
DOI: 10.3390/cryst8020095
|View full text |Cite
|
Sign up to set email alerts
|

Ultra-Wide-Bandwidth Tunable Magnetic Fluid-Filled Hybrid Connected Dual-Core Photonic Crystal Fiber Mode Converter

Abstract: Abstract:We propose a tunable magnetic fluid-filled hybrid photonic crystal fiber mode converter. Innovative design principles based on the hybrid connected dual-core photonic crystal fiber and magnetically modulated optical properties of magnetic fluid are developed and numerically verified. The mode converter was designed to convert LP 11 in the index-guiding core to the LP 01 mode in the photonic bandgap-guiding core. By introducing the magnetic fluid into the air-hole located at the center of the photonic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…The characteristics of the studied modes are obtained using the full vectorial finite difference method (FVFDM) via the Lumerical software package 32 . In terms of the device length (L D ), thermal tunability, and crosstalk, the operation of the reported mode converter outperforms that of similar devices 27 30 , recently presented in the literature.…”
Section: Introductionmentioning
confidence: 77%
See 3 more Smart Citations
“…The characteristics of the studied modes are obtained using the full vectorial finite difference method (FVFDM) via the Lumerical software package 32 . In terms of the device length (L D ), thermal tunability, and crosstalk, the operation of the reported mode converter outperforms that of similar devices 27 30 , recently presented in the literature.…”
Section: Introductionmentioning
confidence: 77%
“…Intermodal coupling in asymmetric dual-core photonic crystal fibers (ADC-PCF) has recently been reported and studied in the context of mode conversion 27 30 . Lin et al 27 have introduced an LP 01 to LP 02 mode converter based on a unique DC-PCF for dispersion adjustment.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…More recently, Yu et al proposed a tunable magnetic fluid-filled hybrid PCF mode converter designed to convert the LP 11 mode in the index-guiding core to the LP 01 mode in the photonic bandgap-guiding core. They found that the coupling efficiency can reach 90% and 95% in the wavelength ranges 1.33-1.85 µm and 1.38-1.75 µm, respectively, with bandwidth values of 520 nm and 370 nm, in a 835 µm long fiber [23].…”
Section: Introductionmentioning
confidence: 99%